DEVELOPMENT AND VALIDATION OF A HPTLC METHOD FOR DETERMINATION OF STRONTIUM RANELATE IN THE PRESENCE OF ITS IMPURITIES - ARTI V. GAJBHAR; V. P. CHOUDHARI; B. S. KUCHEKAR (International Journal of Pharma and Bio Sciences, 2015)
Impurity profiling has gained importance in modern pharmaceutical analysis due to the fact that an unidentified, potentially toxic impurity are hazardous to health and in order to increase the safety of drug therapy, impurities should be identified and determined by selective methods. Thus a simple sensitive high performance thin layer chromatographic (HPTLC) method for estimation of Strontium ranelate and its impurities has been developed. Strontium ranelate and its impurities were separated and identified on silica Gel 60 F254TLC plates with Acetonitrile : Methanol: Ethyl acetate: Formic acid 9:1:1:1 (v/v) as mobile phase. The quantification was performed at λ = 320 nm. The method was validated for linearity, accuracy, precision and robustness according to ICH guidelines. The calibration plots were linear in the range 4000-9000 and 40-90 ng/band for API and its two impurities respectively. The developed method can be used as a quality control tool for Strontium ranelate impurity profile study.